Nucleus Reuniens Afferents in Hippocampus Modulate CA1 Network Function via Monosynaptic Excitation and Polysynaptic Inhibition - Goswamee, Priyodarshan; Leggett, Elizabeth; McQuiston, A. Rory (Frontiers in Cellular Neuroscience, 2021)
The thalamic midline nucleus reuniens modulates hippocampal CA1 and subiculum function via dense projections to the stratum lacunosum-moleculare (SLM). Previously, anatomical data has shown that reuniens inputs in the SLM form synapses with dendrites of both CA1 principal cells and inhibitory interneurons. However, the ability of thalamic inputs to excite the CA1 principal cells remains controversial. In addition, nothing is known about the impact of reuniens inputs on diverse subpopulations of interneurons in CA1. Therefore, using whole cell patch-clamp electrophysiology in ex vivo hippocampal slices of wild-type and transgenic mice, we measured synaptic responses in different CA1 neuronal subtypes to optogenetic stimulation of reuniens afferents. Our data shows that reuniens inputs mediate both excitation and inhibition of the CA1 principal cells. However, the optogenetic excitation of the reuniens inputs failed to drive action potential firing in the majority of the principal cells. While the excitatory postsynaptic currents were mediated via direct monosynaptic activation of the CA1 principal cells, the inhibitory postsynaptic currents were generated polysynaptically via activation of local GABAergic interneurons. Moreover, we demonstrate that optogenetic stimulation of reuniens inputs differentially recruit at least two distinct and non-overlapping subpopulations of local GABAergic interneurons in CA1. We show that neurogliaform cells located in SLM, and calretinin-containing interneuron-selective interneurons at the SLM/stratum radiatum border can be excited by stimulation of reuniens inputs. Together, our data demonstrate that optogenetic stimulation of reuniens afferents can mediate excitation, feedforward inhibition, and disinhibition of the postsynaptic CA1 principal cells via multiple direct and indirect mechanisms.